SENI PERTUNJUKAN WAYANG GOLEK SEBAGAI DAYA TARIK PARIWISATA BUDAYA DI SAUNG ANGKLUNG UDJO - Priyanto, Priyanto; Musthofa, Budiman Mahmud (UI Scholars Hub, 2020)
Wayang golek performance art combines elements of drama, sound, literature, music, movement and fine arts. It can be said that the art of wayang golek performance is a